Pengaruh Kualitas Produk, Kualitas Layanan, dan Citra Merek terhadap Kepuasan Konsumen yang berdampak pada Loyalitas Konsumen - Henderik Zaputera; Amri Amri; Adrian Radiansyah (JEM Jurnal Ekonomi dan Manajemen, 2019)
This study aims to analyze the effect of product quality, service quality, and brand image on consumer satisfaction and its impact on consumer loyalty in the Agunta Drinking Water Company (AMDK). The analysis technique used in this research is path analysis. The results concluded that product quality and service quality variables have a significant and positive effect on customer loyalty. However, brand image variables do not significantly influence consumer satisfaction. The study also concluded that the variable of customer satisfaction has a positive and significant impact on consumer loyalty